(untitled) (Journal of Humanities and Social Sciences Research, 2023)
The aim of the study was to prepare and apply the construction of educational units according to the active learning strategy according to Thelin’s model, and to identify the impact of the active learning strategy according to Thelin’s model supported by hypermedia in learning some soccer skills. The researcher used the experimental approach to suit it with the nature of the problem and the objectives of the research, as the experimental approach is considered one of the best scientific research approaches to solve problems in a practical way, which is defined as the objective observation of a specific phenomenon that occurs in a situation characterized by the exact accuracy of a variable (factor) or more diverse, while the variables are fixed other (factors). Where the researcher intentionally identified the research community from the students of Ash- Shaheed Talib Al-Suhail Preparatory School for the Distinguished in the Third Directorate of Education of Baghdad Al-Karkh for the academic year 2022-2023, whose number is 106 students. As for the research sample, it was chosen by the systematic random method (lottery), as it consisted of fifth grade preparatory students, with four divisions, Division A 35 students, Division B 35 students, Division C 34 students, and Division D 38 students. The systematic random method was used to determine the two research groups. As Division (A) was chosen to be an experimental group and Division (D) a control group, and the lists of each group for research consisted of 16 students, and thus the research sample consisted of (32) students, who constitute 40% of the research community. As this percentage is representative and real for the research community, the exploratory experiment was applied by selecting (15) students from (C and B) to represent the sample of the exploratory experiment for testing and skill, and (10) students from Division B for the exploratory experiment from Division B. The researcher conducted a pre-test for the skills under study, and educational units were implemented at the rate of two units per week, the time of the unit was 45 minutes.